Kecanduan game online pada siswa Sekolah Menengah Atas (SMA): Benarkah menyebabkan penurunan motivasi belajar? - Vina, Inayah; Suroso; Karolin Rista (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between online game addiction and learning motivation in high school students. This study uses a quantitative approach using the product moment correlation technique. This study used subjects totaling 133 high school students by collecting data using Google Forms. This study uses two scales, namely the online game addiction scale and the learning motivation scale. The data collection instrument in this study was to use a Likert scale. The sampling technique used non-probability sampling techniques. Based on the results of data analysis that has been carried out using the SPSS computer program version 16.0 (Statistical Product and Service Solution) for Windows. Based on these results it can be concluded that there is a significant negative relationship between online game addiction and learning motivation in high school students. This means that the higher the online game addiction, the lower the learning motivation, and vice versa, the lower the online game addiction, the higher the learning motivation of high school students. Keywords: Learning Motivation, Online Game Addiction